2023
DOI: 10.1136/bmjgast-2022-001066
|View full text |Cite
|
Sign up to set email alerts
|

Age-related experiences of colorectal cancer diagnosis: a secondary analysis of the English National Cancer Patient Experience Survey

Abstract: ObjectiveThe incidence of colorectal cancer (CRC) in people aged <50 years has been increasing dramatically in the past three decades and such patients are known to face difficulties in diagnosis. The objective of this study was to better understand the diagnostic experiences of patients with CRC and explore age-related differences in the proportion with positive experiences.MethodA secondary analysis of the English National Cancer Patient Experience Survey (CPES) 2017 was conducted on the responses of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…As in other studies, older cancer survivors are more likely to accept cancer and, as a result, report lower anxiety, depression, and suicide than younger adult cancer survivors 22,23 . Different from younger adults who have more negative beliefs about cancer, middle‐aged and older adults have an awareness that cancer is an ongoing chronic condition 24,25 . For this age group, fear may be temporary; moving towards a state of living with cancer as a chronic illness leads to adaption, reduction of fear, overcoming illness and planning for the future 26,27 .…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…As in other studies, older cancer survivors are more likely to accept cancer and, as a result, report lower anxiety, depression, and suicide than younger adult cancer survivors 22,23 . Different from younger adults who have more negative beliefs about cancer, middle‐aged and older adults have an awareness that cancer is an ongoing chronic condition 24,25 . For this age group, fear may be temporary; moving towards a state of living with cancer as a chronic illness leads to adaption, reduction of fear, overcoming illness and planning for the future 26,27 .…”
Section: Discussionmentioning
confidence: 79%
“…22,23 Different from younger adults who have more negative beliefs about cancer, middle-aged and older adults have an awareness that cancer is an ongoing chronic condition. 24,25 For this age group, fear may be temporary; moving towards a state of living with cancer as a chronic illness leads to adaption, reduction of fear, overcoming illness and planning for the future. 26,27 Furthermore, under the influence of traditional philosophies and religious beliefs, including 'zhong sheng an si', 'spiritual immorality and the afterlife', 'life and death unified', 'fate' and 'cause and effect', our participants attributed cancer to fate or karma, considering this approach important for improving physiological and psychological well-being.…”
Section: Category 3: Family Members Suffering Worsementioning
confidence: 99%
“…Further, based on milestone markers highlighted in the survey, on average, participants experienced their CRC diagnostic process during their early 40s and the process took 1–2 years from symptom onset. Similarly, studies have found that younger age groups face more difficult diagnostic paths and less positive diagnosis-related care experiences than do older age groups [ 31 , 32 , 33 ]. The observed trends concerning EAO cancers suggest a need to encourage symptom awareness, screening, and seeking of medical aid amongst younger individuals to improve upon earlier detection [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the three levels of tumor prevention, the most important one is primary prevention, which reduces the incidence of the disease by reducing the associated risk factors. As a result, research into the causative factors of colorectal cancer remains ongoing, with age, gender, and race recognized as contributing factors to its incidence [4,5]. As an external risk factor, diet is a crucial factor in the development of colorectal cancer as it affects the intestinal microenvironment [6].…”
Section: Introductionmentioning
confidence: 99%